2015
DOI: 10.1177/0018720815609501
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cell Phone and Text Message Conversations on Simulated Street Crossing

Abstract: Sending and receiving text messages negatively impact a range of real-world behaviors. These results may inform personal and policy decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…The type of phone use that has been of most concern has been texting, where the pedestrian is looking down, rather than at their surroundings (e.g. Saltos et al, 2015;Banducci et al, 2016). In our study, 5.6% of pedestrians were looking down at their phones, which was similar to the older study of 5.7% in Las Vegas but lower than for the college campuses (8%) and Seattle (7.3%).…”
Section: Implications For Road Safety Campaignssupporting
confidence: 68%
See 1 more Smart Citation
“…The type of phone use that has been of most concern has been texting, where the pedestrian is looking down, rather than at their surroundings (e.g. Saltos et al, 2015;Banducci et al, 2016). In our study, 5.6% of pedestrians were looking down at their phones, which was similar to the older study of 5.7% in Las Vegas but lower than for the college campuses (8%) and Seattle (7.3%).…”
Section: Implications For Road Safety Campaignssupporting
confidence: 68%
“…Pedestrians using phones have been shown to experience cognitive distraction, reduction in their awareness of their surroundings and situation, reduced perceptual visual field, and reduced attention (e.g. Hatfield & Murphy, 2007;Hyman et al, 2010;Stavrinos et al, 2011;Nasar & Troyer, 2013;Alejalil & Davoodi, 2016;Banducci et al, 2016). These behaviors puts pedestrians at higher risk of collision with a motor vehicle (Schwebel et al, 2012;Nasar & Troyer, 2013).…”
Section: Previous Research On Pedestrian Mobile Phone Usementioning
confidence: 99%
“…This is consistent with previous literature, where simulator studies have shown the detrimental effects of dual-tasking on street crossing performance. These studies found that the need for decision making and planning was greater in texting while walking scenarios, thus requiring participants to physically divert their attention from the crossing scene [20]. Another simulator study, assessing dual-task performance in a virtual reality environment where participants crossed a simulated street by walking on a treadmill, found that older adults at risk of falls experienced more collisions with oncoming cars and had longer street crossing times [21].…”
Section: Discussionmentioning
confidence: 99%
“…Not only is typing on a cellular device while walking relatively common, the associated dangers have been recently exposed in the New York Times, U.S. News, CNN, and USA Today (Griggs, 2014;Preidt, 2014;Reynolds, 2014;Watson, 2014). The hazards of texting while walking have also been revealed in empirical studies indicating that such dual tasking hinders the ability to safely cross a street (Banducci et al, 2016), navigate to a target (Lamberg & Muratori, 2012), and identify visual cues consistent with situational awareness (Lim et al, 2015). A weakness of the study is that we did not record any temporal measures related to dialing that would allow for the determination of whether dialing speed changed over the course of the trial and whether participants tended to chunk their responding in synchrony with their gait to facilitate attention shifting (Janssen & Brumby 2010;Janssen, Brumby, & Garnett, 2012).…”
Section: Discussionmentioning
confidence: 99%